Antiplatelet and antibacterial activities of Essential Oils obtained from rhizomes and leaves of Hedychium coronarium J. Koening - Guzmán, Luis (2020)
Hedychium coronarium J. Koening, belonging to Zingiberaceae family, is a perennial herb with fleshly aromatic rhizomes. There are no information about the antiplatelet properties of essential oils (EOs) from rhizomes (HCR) and leaves (HCL) of this herb, additionally, there are reports about the antibacterial activity of the Zingiberaceae species, however, no studies have been carried out in the Colombian Amazon Region. The EOs were characterized by GC-MS, the antiaggregant activity was assessed by ADP and Collagen as platelet agonist and the antibacterial activity against E. faecalis and S. aureus were evidenced by the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). A high content of oxygenated monoterpenes were found in HCL essential oil (EO) and 20 compounds were identified in HCR EO. The HCL EO showed antiaggregant activity when collagen was used and HCR EO showed a concentration-dependent activity against ADP and collagen, meanwhile only the HCR EO showed antibacterial activity against E. faecalis and S. aureus.